Cell-extrinsic autophagy in mature adipocytes regulates anti-inflammatory response to intestinal tissue injury through lipid mobilization - Richter, FC; Friedrich, M; Pohin, M; Alsaleh, G; Guschina, I; Wideman, SK; Johnson, E; Borsa, M; Piletic, K; Hahn, P; Schipper, HS; Edwards, CM; et al. (Cold Spring Harbor Laboratory, 2021)
Autophagy is a critical cellular recycling pathway which is genetically linked to the development of intestinal inflammation in humans. Inflammation drives adipose tissue breakdown and provision of major nutrients such as free fatty acids (FFA). However, the effect of autophagy-mediated FFA release by adipocytes in immune-mediated inflammatory diseases remains unexplored.